Replacing Renewable Energy in Iranian Industries Using Optimal Models - Jalalimajidi, Mohsen; Seyedhosseini, S. M. (International Journal of Energy Economics and Policy, 2017)
In this paper, in order to maximize optimization in Iranian industries , an optimal control modeling has been designed, and then optimal paths of replacing fossil fuels by renewable energy over time is plotted in industrial sectors of Iran. Moreover, a developed optimal control model is presented, and the data used is evaluated. Finally, the estimated energy demand in different industrial sectors of Iran and the costs of fossil fuel extraction is proposed. Keywords: Iranian Industries, Optimization, Renewable Energy JEL Classifications: C32; O13; O47